2013
DOI: 10.1007/s00125-013-3135-2
|View full text |Cite
|
Sign up to set email alerts
|

IL-17A increases the expression of proinflammatory chemokines in human pancreatic islets

Abstract: Aims/hypothesis Cytotoxic T cells and macrophages contribute to beta cell destruction in type 1 diabetes at least in part through the production of cytokines such as IL-1β, IFN-γ and TNF-α. We have recently shown the IL-17 pathway to be activated in circulating T cells and pancreatic islets of type 1 diabetes patients. Here, we studied whether IL-17A upregulates the production of chemokines by human pancreatic islets, thus contributing to the build-up of insulitis. Methods Human islets (from 18 donors), INS-1E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
38
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 50 publications
(91 reference statements)
8
38
0
Order By: Relevance
“…In experimental autoimmune encephalomyelitis, most pathogenic IFN-g-producing cells were derived from Th17 cells in chronic inflammatory settings (26). In the present study, we observed a remarkable increase in the IFN-g/IL-17 ratio in highly purified Th17 cells from children with advanced b cell autoimmunity and clinical type 1 diabetes, suggesting a similar shift from the Th17 phenotype toward the Th1/ (6,8,11).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In experimental autoimmune encephalomyelitis, most pathogenic IFN-g-producing cells were derived from Th17 cells in chronic inflammatory settings (26). In the present study, we observed a remarkable increase in the IFN-g/IL-17 ratio in highly purified Th17 cells from children with advanced b cell autoimmunity and clinical type 1 diabetes, suggesting a similar shift from the Th17 phenotype toward the Th1/ (6,8,11).…”
Section: Discussionsupporting
confidence: 65%
“…IL-17 increased b cell apoptosis and upregulated the expression of stress response genes and proinflammatory chemokines in b cells (6,8,11). Accordingly, the upregulation of Th17 immunity could contribute to the destruction of b cells and the development of type 1 diabetes.…”
mentioning
confidence: 99%
“…Under our experimental conditions, however, activation of STAT-regulated pathways cannot explain the phenotype induced by NMI KD. Thus, we observed that NMI KD increases cytokine-induced apoptosis in INS-1E and human islet cells, whereas STAT1 KD protects beta cells against cytokine-induced apoptosis (34,50,69). Furthermore, STAT1 silencing decreases NO production in cytokinetreated beta cells (50), whereas NMI KD does not change it (Fig.…”
Section: Discussionmentioning
confidence: 61%
“…The same medium, but with 2% FBS, was used during the cytokine treatment as described (34). The human embryonic kidney cells HEK293T were cultured in DMEM containing 25 mM glucose, 5% FBS, 100 units/ml penicillin, 100 g/ml streptomycin, and sodium pyruvate 100ϫ (Invitrogen).…”
Section: Culture Of Human Islet Cells Facs-purified Rat Beta Cells mentioning
confidence: 99%
“…Insulitis occurs in the context of a "dialog" between invading immune cells and the target pancreatic b-cells (1), which includes upregulation of islet human leukocyte antigen (HLA) class I expression in b-cells (2) and production of chemokines such as CXCL10 by the islet cells (3)(4)(5).…”
mentioning
confidence: 99%